PHYSICAL ACTIVITY LEVEL, FUNCTIONAL MOBILITY AND FALL RISK IN THE ELDERLY - Silva, Raesa Andrade da; Brandão, Glaudson Sá; Silva, Anderson Soares; Urbano, Jessica Julioti; Oliveira, Ezequiel Fernandes de; Oliveira, Luis Vicente Franco; Camelier, Aquiles Assunção; Brandão, Glauber Sá (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: Low levels of physical activity and functional mobility lead to greater difficulty in performing activities of daily living and are directly proportional to mortality in the elderly. Thus, there are the need to create mechanisms linked to the maintenance of the functional capacity, which assure the elderly autonomy and self-confidence. Objective: To verify the level of physical activity and functional mobility in the elderly and if this functional mobility suffers interference of the age group and physical activity. Methods: The study involved the elderly aged 60 and over, living in Senhor do Bonfim (BA), in the northeastern region of Brazil, from February to July 2015. The evaluation of the subjects occurred in a single session, with physical and general clinical evaluation, as well as the collection of sociodemographic, anthropometric and self-reported morbidities through the application of questionnaires. It was also carried out the Timed Up and Go test (TUG) to verify the levels of functional mobility and level of physical activity with application of the International Questionnaire of Physical Activity (IPAQ) adapted for the elderly. Results: In this study, 127 patients were studied, predominantly female (87%) and mean age of 68 ± 7 years, and the majority of the elderly corresponded to the age group of 60 to 69 years. The elderly belonging to the group considered inactive (IPAQ up to 150 min/weekly) presented the execution time of TUG higher than the elderly in the group considered active (IPAQ > 150 min/weekly), with averaging time for carrying out the test of 10.5±2 minutes and 8.9±2 minutes respectively, with a statistically significant difference of p<0.01. And the execution time of TUG increased proportionally to the increase of the age group. Conclusion: Elderly with lower level of physical activity and belonging to the higher age groups present a higher risk of falls. Strategies should be developed to stimulate increased physical activity level and functional mobility of this population, especially among the older ones, reducing the incidence of falls and providing greater autonomy.